Surgical Treatment of Chronic Osteomyelitis - M. R. Garaev; V. S. Panteleev; M. A. Nartaylakov; V. D. Dorofeev; D. V. Inyushev; D. S. Golkov (Креативная хирургия и онкология, 2019)
Introduction. In this study, we analysed the results of applying various surgical methods in the combined treatment of inflammatory diseases of bones and joints.Materials and methods. The work was based on data from a multi-dimensional cohort study using non-concurrent (historical) control. A retrospective study included the analysis of medical records covering the period of 2009–2016 (1059 patients). A prospective study consisted in analysing the effectiveness of modern surgical methods in the combined treatment of inflammatory diseases of bones and joints in patients hospitalised to the Septic Surgery Department of the G.G. Kuvatov Republican Clinical Hospital (Ufa, Russia) in 2017–2018 (285 patients).Results and discussion. An analysis of the authors’ own data revealed that injuries (73.21%) and infectious complications after receiving surgery on bones and joints (15.03%) are the most common causes of osteomyelitis. In most cases, the following list of measures is optimal for diagnosing suspected osteomyelitis of various etiologies: X-ray, general clinical tests supplemented by the fistulography or CT of the affected area prior to surgery, as well as the examination of surgical material after surgery. The use of modern methods for surgical debridement and surgical repair of bone defects in the combined treatment of patients with chronic osteomyelitis can significantly reduce the relapse rate. It is recommended that patients with osteomyelitis be treated at large in-patient surgical facilities, which include a specialised department for the treatment of surgical infections and corresponding support services.Conclusion. Apparently, there is no one most optimal method for treating osteomyelitis. The optimal effect in the treatment of osteomyelitis is achieved through a personalised set of therapeutic measures using the following methods: laser vaporisation, negative-pressure wound therapy, ultrasonic cavitation in the focus of inflammation, as well as surgical repair of the post-trepanation bone defect or wound.